Unpacking Teachers’ Experiences of Teaching Writing at the Undergraduate (Bachelor) Level in Nepal (Journal of NELTA, 2021)
Teachers’ experiences prove that second language writing (L2 writing) is a challenging task. Embracing a phenomenological approach to research, this study unpacks teachers’ lived experiences of teaching English as a second language (ESL) writing at the undergraduate (bachelor) level in Nepal. Specifically, it explores how teachers teach writing, what kind of assignments they assign to their students, what they feel comfortable and uncomfortable with teaching writing, what they want to improve in their teaching, and what their students struggle with in carrying out their assignments. For collecting data, I used a written open-ended questionnaire as a research tool and I analyzed the resulting data thematically. The study reveals that, out of nine teachers, only four strove to embrace a process approach to writing. The findings show that, as reported by the teachers, students most often react negatively to writing assignments and struggle in their writing. The teachers assign several long and short assignments, and, by their responses, it can be understood that all intended to improve their teaching, ranging from coherence and cohesion to contextualizing their teaching.